2004
DOI: 10.2519/jospt.2004.34.10.610
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Musculoskeletal Disorders of the Hand and Wrist: Epidemiology, Pathophysiology, and Sensorimotor Changes

Abstract: The purpose of this commentary is to present recent epidemiological findings regarding work-related musculoskeletal disorders (WMSDs) of the hand and wrist, and to summarize experimental evidence of underlying tissue pathophysiology and sensorimotor changes in WMSDs. Sixty-five percent of the 333 800 newly reported cases of occupational illness in 2001 were attributed to repeated trauma. WMSDs of the hand and wrist are associated with the longest absences from work and are, therefore, associated with greater l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
122
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(133 citation statements)
references
References 115 publications
(176 reference statements)
7
122
0
4
Order By: Relevance
“…Exposure to workpace dependent on the technical organization, which could represent a measure of the repetitiveness of the task, increased the risk of DQD. This agrees with previous studies on hand-wrist tendonitis (12,13,16,31,34,35). The multifactorial nature of disorders involving several biomechanical and organizational factors is coherent with the literature reporting higher risk of hand-wrist tendinitis for combined exposure to work-related risk factors (13,32).…”
Section: Petit Le Manac'h Et Alsupporting
confidence: 82%
See 2 more Smart Citations
“…Exposure to workpace dependent on the technical organization, which could represent a measure of the repetitiveness of the task, increased the risk of DQD. This agrees with previous studies on hand-wrist tendonitis (12,13,16,31,34,35). The multifactorial nature of disorders involving several biomechanical and organizational factors is coherent with the literature reporting higher risk of hand-wrist tendinitis for combined exposure to work-related risk factors (13,32).…”
Section: Petit Le Manac'h Et Alsupporting
confidence: 82%
“…This confirms results for hand-wrist tendinitis observed among workers highly exposed to wrist flexion/extension (16), pronation/supination (13) and, more generally, sustained or repeated postures of the hand and wrist (13,25,30,31,32). The influence of postural factors on the risk of DQD seems to be higher and more significant for DQD than for the other upper-extremity MSD in this working population (21).…”
Section: Petit Le Manac'h Et Alsupporting
confidence: 76%
See 1 more Smart Citation
“…Barr et al (2004) found that repetitive hand movements contributed in the development of MS disorders in the hand and wrist. In addition, Werner et al (2005) reported that repetitive hand movements were associated with upper extremity pain and discomfort.…”
Section: Comparisons and Contributions To The Literaturementioning
confidence: 99%
“…Chronic musculoskeletal pain conditions such as repetitive strain injury and tendonitis are clearly associated with peripheral tissue damage that includes inflammation of the muscle (Barr and Barbe, 2002;Barr et al, 2004;Stauber, 2004). Data from the Bureau of Labor and Statistics states that 53% of the private workforce had musculoskeletal pain over the last 2 weeks, and 13% of these lost productive work time with losses estimated at $61 billion per year.…”
Section: Introductionmentioning
confidence: 99%